Opioid medication doses among safer supply clients: Current safer supply doses and previous OAT experience - Gillian Kolla; Kaitlin Fajber; Andrea Sereda; Cassidy Morris; Perri Deacon; Lauren E. Cipriano (Drug and Alcohol Dependence Reports)
Introduction: Safer opioid supply (SOS) is a harm reduction approach to prescribing pharmaceutical opioids to people at high risk of overdose from the toxic unregulated drug supply. Previous research demonstrates positive health outcomes and reductions in overdose mortality among SOS clients; however few reports describe previous opioid agonist treatment history prior to initiating SOS, or the medication combinations and doses prescribed within SOS programs. Methods: We used convenience sampling to collect survey data from 95 SOS program clients in London, Canada. We use descriptive statistics to analyze survey data and report on OAT history prior to initiating SOS, including maximum methadone dose. We also report on current SOS medication combinations and doses. Findings: Previous experience with OAT was common and reported by 87 % of SOS clients. Mean highest dose of methadone ever received was 95 mg (range: 20–200 mg), with close to 40 % reporting doses of ≥ 120 mg. 95 % of SOS clients reported prescriptions for immediate-release tablet hydromorphone; 28 % were receiving hydromorphone monotherapy; 68 % were receiving hydromorphone alongside a long-acting opioid, and 5 % receiving hydromorphone alongside 2 long-acting opioids. Total average milligram morphine equivalent (MME) doses of combination SOS prescriptions (MME 1616) were similar to high dose methadone (120 mg = MME 1440). Conclusions: Previous high dose OAT experience was common among SOS clients prior to enrollment in the SOS program. Our results may inform the individualization of high dose opioid prescriptions for people with high tolerance due to exposure to unregulated fentanyl.